Η ΣΤΡΑΤΙΩΤΙΚΗ ΚΑΙ Η ΠΟΛΙΤΙΚΗ ΚΡΙΣΗ ΣΤΗΝ ΕΛΛΑΔΑ ΤΟΝ ΑΠΡΙΛΙΟ ΤΟΥ 1941 - ΚΟΛΙΟΠΟΥΛΟΣ ΙΩΑΝΝΗΣ Σ. (Μνήμων, 1977)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Δεν παρατίθεται περίληψη. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>